Parental intervention strategies to reduce screen time among preschool-aged children: a systematic review - Raj, Diana; Mohd Zulkefli, Nor Afiah; Minhat, Halimatus Sakdiah; Ahmad, Norliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Aims: Children below five years have been the target of screen time guidelines. The adverse health outcomes associated with it require focusing on prime strategies for reducing screen time. The current study reviews parental intervention strategies to reduce screen time among preschool-aged children. Design: Systematic review. Data sources: A total of five databases of the Cochrane register of controlled trials, CINAHL, Medline PubMed, and Scopus databases were searched from May 1 to 31, 2020. Review Methods: The keywords of “screen time”, “television”, “video”, “computer”, “mobile device”, “hand phone”, “media use”, “preschool-aged children”, “interventions”, and “strategies” used for search. The inclusion criteria are limited to specific study populations, intervention, comparison and outcomes (PICOs), language, and published study types. The quality of articles was assessed using the Cochrane Risk of Bias (RoB) tool. Results: A total of six studies that met the inclusion criteria were further analysed. It showed that besides providing knowledge and awareness regarding screen time, restrictive practices, offering alternative activities to parents and removing the screen from the child’s bedroom were the most common strategies used by successful studies. The duration of intervention between 6-8weeks was sufficient to observe screen time reduction, while faceto-face methods dominated the mode of delivery. Increasing parental self-efficacy, listing outcome expectations, and reinforcement strategies targeting both the parents and their home environment were beneficial in reducing screen time. Conclusion: Future screen time reduction studies could benefit from incorporating the above approaches for screen time reduction intervention among preschool children.